2009
DOI: 10.1016/j.icarus.2008.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Titan solar occultation observed by Cassini/VIMS: Gas absorption and constraints on aerosol composition

Abstract: solar occultation observed by Cassini/VIMS: gas absorption and constraints on aerosol composition, Icarus (2009), doi: 10.1016/j.icarus.2008.12.024 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
112
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(131 citation statements)
references
References 40 publications
(37 reference statements)
18
112
0
Order By: Relevance
“…We used the HITRAN2008 database for the CO 2 and CO linelists. An unidentified feature near 4.3 μm was previously reported (Bellucci et al 2009). We found that most of that feature can be attributed to the ν 3 +ν 6 band of C 2 H 6 (Brown, 2012, priv.…”
Section: Radiative Transfer Modelingsupporting
confidence: 60%
See 4 more Smart Citations
“…We used the HITRAN2008 database for the CO 2 and CO linelists. An unidentified feature near 4.3 μm was previously reported (Bellucci et al 2009). We found that most of that feature can be attributed to the ν 3 +ν 6 band of C 2 H 6 (Brown, 2012, priv.…”
Section: Radiative Transfer Modelingsupporting
confidence: 60%
“…Although linelists for the 1−2 μm bands of CH 4 have been included in HITRAN and have been used for the analysis of Titan spectra (Bellucci 2008;Bailey et al 2011), significant discrepancies may remain between these linelists and laboratory data Karkoschka & Tomasko 2010). The lack of information on CH 4 weak lines in HITRAN severely limits the derivation of haze opacities from the VIMS spectra.…”
Section: Radiative Transfer Modelingmentioning
confidence: 99%
See 3 more Smart Citations